Association between Cyclic Threshold Values and Clinical Symptoms in Patients with COVID-19 at Teaching Hospital, Jumla, Karnali, Nepal - Rai, Maya; Neupane, Ganesh Prasad; Kumar, Anil; Singh, Lokjan; Lohani, Sarswati; Thakur, Kundan (Journal of Nepalgunj Medical College, 2023)
Introduction: The cyclic threshold (CT) value obtained in the reverse transcriptase polymerase chain reaction (RT-PCR) has been used as the surrogate marker of viral load. Therefore, to understand viral kinetics and evaluate the disease severity with clinical symptoms, it is necessary to evaluate cyclic threshold value in COVID-19-infected patients. Aims: To assess association between cyclic threshold value and clinical symptoms in patients with COVID-19. Methods: A descriptive cross- sectional study was conducted on PCR-positive patients (n=208) for six months at Karnali Academy of Health Science, Teaching Hospital Jumla. The RT-PCR was performed and data of the cyclic threshold value of PCR-positive patients was taken from the laboratory in predesigned study proforma. Data entry and analysis were done in SPSS version 20.0. Results: A larger proportion of females (65.9%) than males (43.1%) had a COVID-19 infection symptoms of COVID-19 were present in about equal numbers of infected males (61%) and females (68.7%). Most of the individuals were in the age range of 19 to 39 years. A cyclic threshold value of less than 30 was present in the majority (49%) of patients. Symptoms were present in 65.9% of individuals. Symptoms were present in a large proportion of subjects with cyclic threshold values of 1–19 and 20–29, at 89.5% and 77.9%, respectively. Conclusion: This study provides valuable insights into the association between cyclic threshold values and clinical symptoms of COVID-19 in patients. It also explores the underlying factors like gender disparities and age-specific disease severity. Patients showing symptoms of COVID-19 typically had a cyclic threshold value below 30 and carry a higher amount of the virus compared to those who don’t show symptoms. The association between signs and symptoms and the cyclic threshold is highly significant.